2006
DOI: 10.1016/j.ecss.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in genetic structure and historical demography of marine and riverine populations of Atherina at similar geographical scales

Abstract: In this paper, we compare the genetic structure and the historical demography of two populations of the sand smelt Atherina boyeri from the rivers Tagus and Mondego (Portugal) with two groups of samples of the closely related marine Atherina presbyter collected on the shore at comparable latitudes. A. presbyter is a pelagic marine inshore fish, while A. boyeri is typically found in coastal lagoons, estuaries and freshwaters bodies. Analysis of mtDNA control region sequences showed that the marine A. presbyter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…Indeed, the estimates derived from the samples of each location may not reXect what happened in the past in that area, but rather the signatures of the demographic events that took place in the locations where the populations survived during the glacial retreats. In the case of A. presbyter, it is plausible that the species might have simply moved south of Iberia, having recolonized the area in the current interglacial (Francisco et al 2006a(Francisco et al , 2008. It is interesting to note that for the southern Portugal population the data conform to the spatial expansion model and the demographic one is rejected.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, the estimates derived from the samples of each location may not reXect what happened in the past in that area, but rather the signatures of the demographic events that took place in the locations where the populations survived during the glacial retreats. In the case of A. presbyter, it is plausible that the species might have simply moved south of Iberia, having recolonized the area in the current interglacial (Francisco et al 2006a(Francisco et al , 2008. It is interesting to note that for the southern Portugal population the data conform to the spatial expansion model and the demographic one is rejected.…”
Section: Discussionmentioning
confidence: 82%
“…between Fonte-da-Telha and Arade). For the same species, Francisco et al (2006a) did not Wnd genetic diVerentiation for smaller geographic scales (less than 250 km). Several other studies using the same marker and similar sampling eVort could not Wnd genetic diVerentiation, even for much wider spatial scales (several hundreds to thousands of kilometres) (e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The western European and Moroccan A. boyeri belongs to the same clade that occurs in the Western Mediterranean and Adriatic Seas and probably survived in the Mediterranean area re-invading Atlantic rivers and lagoons after the last glaciation (Francisco et al, 2006).…”
Section: Biogeographical Implicationsmentioning
confidence: 94%
“…Recently, we have proposed an evolutionary pattern of the three species of the A. boyeri complex [20], including firstly sympatric speciations followed by a post-Pleistocene colonization of the lagoons. Similarly, it has been suggested that during the cold periods, fish of the A. boyeri complex probably went extinct from the Portuguese coasts and present populations are due to recent recolonizations from western Mediterranean refugia [21]. The presence of Atherina populations around the Tunisian Islands gave us the opportunity to obtain new data concerning the evolution of the A. boyeri species complex, constituting thus the aim of this study.…”
Section: Introductionmentioning
confidence: 99%